Intro to Analysis in-class_Part_37

# Intro to Analysis in-class_Part_37 - 5.4 Higher derivatives...

This preview shows pages 1–2. Sign up to view the full content.

5.4 Higher derivatives and Taylor’s Thm 79 Proof. Suppose p is a polynomial in ( x - a ): p ( x ) = c 0 + c 1 ( x - a ) + ··· + c n ( x - a ) n . After k diﬀerentiations, the terms c 0 ,...,c k - 1 vanish: p ( k ) ( x ) = k ! c k + (terms with ( x - a ) as a factor) . So p ( k ) ( a ) = k ! c k . If f ( x ) and p ( x ) have n th -order agreement, f ( k ) ( a ) = k ! c k = c k = f ( k ) ( a ) k ! , k = 1 ,...,n. Theorem 5.4.5 (Taylor’s Thm) . Suppose f C n +1 ( I ) for some open interval I contain- ing a and x . Then for some c between a and x , f ( x ) = f ( a ) + f 0 ( a )( x - a ) + 1 2 f 00 ( a )( x - a ) 2 + ··· + 1 n ! f ( n ) ( a )( x - a ) n + R n ( x ) , R n ( x ) = f ( n +1) ( c ) ( n + 1)! ( x - a ) n +1 . NOTE: c depends on x , so RHS of f is not a polynomial ; f ( n +1) ( c ) is not a constant. Proof. We show the theorem holds at x = b . Let P be deﬁned by P ( x ) = T n ( a,x ) + C ( x - a ) n +1 , where C is chosen so that f ( b ) = P ( b ), i.e., C = f ( b ) - T n ( a,b

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 11/26/2011 for the course MAT 4944 taught by Professor Wong during the Fall '11 term at FSU.

### Page1 / 2

Intro to Analysis in-class_Part_37 - 5.4 Higher derivatives...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online